2020
DOI: 10.1016/j.ejca.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DNA damage repair defects on response to radium-223 and overall survival in metastatic castration-resistant prostate cancer

Abstract: Radium-223 is a targeted alpha radiation therapy for metastatic castration-resistant prostate cancer. DNA damage repair (DDR) defective prostate cancers, specifically genetic aberrations leading to homologous recombination deficiency (HRD), accumulate irreparable DNA damage following genotoxic treatment. This retrospective study assessed DDR mutation status in patients treated with radium-223, investigating their association with efficacy and overall survival (OS). Patients and methods: Included patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 21 publications
(24 reference statements)
5
38
0
Order By: Relevance
“…Recent studies have shown an OS benefit in patients with mCRPC that have genetic aberrations associated with homologous recombination deficiency (HRD) receiving radium‐223. As we did not have this data, we were unable to control for the presence or absence of HRD in our cohorts or its potential impact on our results 32,33 . Finally, data collection was dependent upon the completeness of the information contained in each chart and reported on the electronic case report form.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent studies have shown an OS benefit in patients with mCRPC that have genetic aberrations associated with homologous recombination deficiency (HRD) receiving radium‐223. As we did not have this data, we were unable to control for the presence or absence of HRD in our cohorts or its potential impact on our results 32,33 . Finally, data collection was dependent upon the completeness of the information contained in each chart and reported on the electronic case report form.…”
Section: Discussionmentioning
confidence: 95%
“…As we did not have this data, we were unable to control for the presence or absence of HRD in our cohorts or its potential impact on our results. 32,33 Finally, data collection was dependent upon the completeness of the information contained in each chart and reported on the electronic case report form.…”
Section: Limitationsmentioning
confidence: 99%
“…(2019) [ 95 ] 190 BRCA2, ATM, CHEK2, ATR, FANCI, FANCL and PALB2) Increased response to radium-223 Van et al. (2020) [ 96 ] 93 DNA repair defects (BRCA2, ATM, CDK12) Increased response to radium-223 CTC, circulating tumor cell; mCRPC, metastatic castration–resistant PCa; PCa, prostate cancer; PSA, prostate-specific antigen; PSCA, prostate stem cell antigen. …”
Section: Genomic Evaluation For Mcrpcmentioning
confidence: 99%
“…It selectively targets the bone microenvironment and emits high-energy alpha particles that cause double-strand DNA breaks [ 91 , 93 ], which exert potent localized cytotoxic effects [ 94 ]. Patients harboring aberrations in DNA repair genes experience a greater benefit from radium-223, relative to patients without these mutations [ 95 , 96 ].…”
Section: Genomic Evaluation For Mcrpcmentioning
confidence: 99%
“…The mutation rates of BRCA1/2 (15% combined), ATR (9%) and ATM (7%) in PCa patients are significantly higher in lethal compared with localized disease and are associated with earlier age at death and shorter PSMA-RLT proteomics/phosphoproteomics 5 5 survival time (5,7). While recent clinical data have associated mutations in DDR genes with response (8) or resistance (9) to alpha-particle therapy, the roles of DDR/RSR and TP53 pathways in modulating responses to RLT in PCa have not been investigated systematically.…”
Section: Introductionmentioning
confidence: 99%